ERWP 2018
DOI: 10.24148/wp2017-17
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Macroprudential Policy to Forecasts of Financial Stability

Abstract: The introduction of macroprudential responsibilities at central banks and financial regulatory agencies has created a need for new measures of financial stability. While many have been proposed, they usually require further transformation for use by policymakers. We propose a transformation based on transition probabilities between states of high and low financial stability.Forecasts of these state probabilities can then be used within a decisiontheoretic framework to address the implementation of a countercyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…15 Basically, the model allows the transition probabilities of the first-order Markov process to depend on covariates t Z . The states of the economy are generally interpreted as low and high financial stability states (see Gadea-Rivas andPerez-Quiros, 2015, andBrave andLopez, 2017). However, this might be misleading in our case.…”
Section: A Markov-switching Framework For the Analysis Of The Bpismentioning
confidence: 87%
See 1 more Smart Citation
“…15 Basically, the model allows the transition probabilities of the first-order Markov process to depend on covariates t Z . The states of the economy are generally interpreted as low and high financial stability states (see Gadea-Rivas andPerez-Quiros, 2015, andBrave andLopez, 2017). However, this might be misleading in our case.…”
Section: A Markov-switching Framework For the Analysis Of The Bpismentioning
confidence: 87%
“…We estimate a univariate first-order autoregressive Markov-switching model as per Hamilton (1989). Following Brave and Lopez (2017), we use the model to capture the joint dynamics between real GDP and private credit growth while incorporating the different BPI versions into the time-varying transition probability model proposed by Diebold et al (1994). The motivation behind this model setting lies in the effort to capture both credit and real economic activity together with the proposed BPIs (again, we also present the results of this exercise for the Financial Cycle Index and the credit-to-GDP gap in Appendix B).…”
Section: A Markov-switching Framework For the Analysis Of The Bpismentioning
confidence: 99%
“…(2013), Anundsen et al. (2016), Brave and Lopez (2019), and Tölö, Laakkonen, and Kalatie (2018). The rationale is that indicators that perform well as an early warning signal are better suited to signal the need for the buffer as well as its release before a banking crisis occurs.…”
Section: Related Literaturementioning
confidence: 98%
“…The first approach is based on early warning models of banking crises or the buildup of macroeconomic vulnerabilities; see, for example, Behn et al (2013), Anundsen et al (2016), Brave andLopez (2019), andTölö, Laakkonen, andKalatie (2018). The rationale is that indicators that perform well as an early warning signal are better suited to signal the need for the buffer as well as its release before a banking crisis occurs.…”
Section: Related Literaturementioning
confidence: 99%
“…Tng and Kwek (2015) detected that an increase in financial stress leads to tighter credit conditions and lower economic activity in five Asian countries (Indonesia, Malaysia, Philippines, Singapore and Thailand). Brave and Butters (2012) showed that increasing financial stress typically leads to sharp downturns in economic activity. Afonso et al (2018) examined the impact of financial stress, using the FSI developed by the International Monetary Fund (IMF), and fiscal developments in a threshold vector autoregressive model (VAR) model for several countries.…”
Section: Literaturementioning
confidence: 99%